FILANTROPI ISLAM DI PASAR MODAL (MODEL WAQAF SAHAM MELALUI SISTEM ONLINE TRADING SYARIAH) - Khabib Musthofa (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
Stock is one type of immovable asset object that is active in Indonesia. The emergence of share waqf built by ijtihad ulama in an effort to maximize the benefits of its recipients amid the Muslim population of Indonesia. In addition, technology factors such as those present (sharia online trading system) that facilitate and accelerate Islamic stock transactions, until now there are six securities in Indonesia that have stock waqf facilities such as BNI Sekuritas, MNC Sekuritas, Henan Putihrai Sekuritas, Samuel Sekuritas. , Panin Sekuritas and Philip Sekuritas. The purpose of this is to see the model for the application of share waqf in Indonesia, as well as to see how the potential of share waqf in Indonesia. This research is a qualitative model which is categorized as a literature study with a descriptive approach. The results show that there are two models of share waqf management rules in Indonesia, namely the waqf model whose object is direct Islamic stocks and the waqf model based on investment returns on Islamic stocks. With share waqf, indirectly investors can immediately do philanthropy. Keywords: Capital Market, Shares, Waqaf